Tradition and Discontinuity: Interrogating the Notions of Normal Science and Revolution in Thomas Kuhn - Michael Sunday Sasa (Universitas Negeri Makassar, 2021)
The present paper is a representation of a systematic inquiry as well as an application of the main thrust in Thomas Kuhn’s discourse concerning the growth of human knowledge represented in philosophy of science. The paper begins by stating the points of tradition and normal science in Thomas Kuhn’s analysis of the growth of scientific knowledge. This is juxtaposed with the notions of discontinuity and revolution. A fundamental point in the paper is that Thomas Kuhn presents an analysis that bring to the fore a tradition of continuous discontinuity. This he expounded in the philosophy of paradigm shifts brought about by crisis and revolution, resulting in the overthrow of an existing hegemony and the birth of a new one. In all, Thomas Kuhn believes that science does not represent a paradigm of rationality because going through the history of science; we are not able to discover a particular paradigm or rationality that runs through the entirety of the history of science. If anything at all, science is made up of different paradigms of rationality, models of knowledge systems of method such that, the change from one scientific epoch to another cannot be a lineal rational or methodic one. Rather, it is a shift from one model to an opposing one; what he calls a gestalt switch which is a change in ‘form of life’, ‘language game’ or ‘conceptual scheme’. The paper however, presents the thesis that even if there is no outstanding form of rationality the history of science is seen to contain a certain continuous tradition. This has to do with the aim of any science. And so, be it the science of Ptolemy, Copernicus or Galileo, Einstein or Newton, there is the aim of human interest transcending all the epochs. To this extent, the paper argues a rationality of any scientific epoch or paradigm must derive from the quality of human interest it potent. Any science be it religion, mysticism or positivism that does not aim at human flourishing is not rational. The paper employs the method of text-analysis, conceptual clarification, constructive criticism and reconstructivism to bring forth its central argument.